Implementation of the Non-Cash Food Assistance Program (BPNT) in Takalar Regency - Rusliadi Rusliadi; Ida Widianingsih; Rd Achmad Buchari (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
Poverty alleviation is one of the efforts to improve the welfare of society. The resulting impact can affect life and the fulfillment of basic needs of society such as food needs. This study aims to analyze the implementation of the non-cash food assistance program in Takalar Regency. The method used in this research is qualitative-explorative to examine the implementation of the non-cash food assistance program as a national initiative to fight poverty. Data was collected from interviews, field observations and existing literature, then Nvivo 12 Pro was used to analyze the results. The location in this study is in Takalar Regency. The research results show that the implementation of the non-cash food assistance program has gone well, such as access to information. However, the findings in this study that were considered less than optimal were related to executor accountability, timeliness, suitability for needs, not on target, and target group coverage.